Treatment outcomes among young persons living with HIV who transitioned to adult care in southern Nigeria: A retrospective cohort study - Esther Nwanja; Uduak Akpan; Otoyo Toyo; Ogheneuzuazo Onwah; Chinazom Ekwueme; Ofonime Dixon-Umo; Bala Gana; Godson Ndubueze; Ijeoma Uchenna Itanyi; Echezona Ezeanolue; Augustine Idemudia; Onyeka Igboelina; et al. (PLoS ONE, 2025)
Background In October 2019, a peer-based transition preparedness model was introduced as part of peer club activities to prepare young persons living with HIV (YLHIV) for adult care. This study compared the 12 and 24 months treatment outcomes of YLHIV who transitioned to adult care in primary, secondary and tertiary health facilities in Southern Nigeria, following the introduction of this model. Materials and methods This was a retrospective cohort study using data extracted from the medical records of YLHIV who transitioned to adult care at 25 years in 2018 and in 2021 across 155 healthcare facilities in southern Nigeria. Baseline data at transition, as well as 12 and 24 months post-transition data were extracted for comparison between those who were transitioned before (2018 cohort) and after (2021 cohort) the transition preparedness model was introduced. Logistics regression analysis was used to compare client continuity on treatment and undetectable viral load between the two groups at 12 and 24 months after transitioning to adult care. Results Most of the1,555 YLHIV who transitioned to adult care in 2018 (n = 343, 22.1%) and 2021 (n = 1,212, 77.9%) were females (91.0% in 2018 v.82.6% in 2021) and initiated ART at 20 years or older (92.7% v. 95.7%). A higher proportion of those in the 2021 cohort were continuously retained both at 12 months and 24 months post-transitioning compared to those in the 2018 cohort (12 months: 96.7% vs 80.2%, p < 0.001; 24 months: 92.7% vs 77.6% p < 0.001). Similarly, the proportion of YLHIV with undetectable viral load in the 2021 cohort was significantly higher than those in the 2018 cohort at both 12 months (96.1% vs 60.1%, p < 0.001) and 24 months (93.3% vs 80.6%, p < 0.001), respectively. Conclusion Peer-based transition preparedness model improved treatment outcomes of YLHIV who transition to adult care. Programs should implement tailored, peer-based interventions to address gaps in service delivery.